Leila Aboulela’s Bird Summons: Iman’s psycho-spiritual quest from trauma to wholeness - Saleh, Lina (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article focuses on the development of Iman’s character in Leila Aboulela’s Bird Summons and shows how she eventually achieves individuation in the British diaspora. The argument hinges upon two assumptions: Iman suffers from an identity crisis which arises from the Syrian Civil War and her three failed marriages, and she manages to overcome this crisis through a psycho-spiritual quest which heals her trauma and enables her to resume her life as a normal person. To achieve its goals, the study utilizes Sigmund Freud’s psychological theories on traumatic neurosis, the seduction hypothesis, repression, and hysteria to prove that Aboulela portrays Iman as an unindividuated character whose divorce experience forces her to go through an abreaction of her repression and traumatized memory which used to impede the normal development of her personality formation. On the other hand, the article draws on Maureen Murdock’s model of the female’s psycho-spiritual quest. Murdock’s eight-stage model functions as a therapeutic process that transforms the protagonist after she confronts her past. The study concludes that the outcome of Iman’s psycho-spiritual quest results in the redemption of the split in her consciousness and unconsciousness caused by traumatic neurosis and in a reconciliation of the feminine and masculine sides of her character, which is needed to achieve wholeness. This identity reconstruction empowers Iman to prevail over war trauma, patriarchal dominance, and the cultural challenges in the British diaspora.